The public library instead of training and educating the public librarian - Jaramillo, Máster Orlanda (2013)
This work shows the relationship between the public library and professional formation, particularly on public librarian profile. The labor arise in context of the research "labor market profile to the  information professional and his belongs with professional formation in Latin America" and the close relation which arounds the subject of the public library, research, publications and the PHD thesis. The document starts from the consideration of the profile set of knowledge, skills and attitudes that defines professional formation, so it is necessary to determine what is basic, what should have and what nurturing a librarian, in other words, establish the public librarian should have core requirements in order to do a social work with efficiency and effectiveness. For this end, we part of two hypotheses: one, the public library as a space by and for the community. The second, related to the public library as an institution that contributes to the formation process of the librarian, since the demands of users, the social-cultural challenges, technological and managerial, who each time this information unit goes directly.